Creating a college adjustment index score for student veterans with and without disabilities - Umucu, Emre (Frontiers in Psychiatry, 2022)
Higher education is a critical public health tool to achieve economic success, upward mobility, and improved quality of life. Yet, certain groups of students, including student veterans with and without disabilities (SVDs), are at high risk for course failure and dropout, partially due to challenges related to college adjustment. The purpose of this study is to develop a new college adjustment index score for SVDs. We had a total of 4 different research studies to examine the psychometric properties of our college adjustment index score. After conducting a series of psychometric analyses, we selected a total of 18-items. This 18-item tool may help clinicians and researchers conceptualize college adjustment among students through the lens of integrative Tinto’s model and positive psychology approaches. Our psychometric analyses revealed that this index tool is brief, reliable, and valid tool to capture college adjustment in SVDs.